2022
DOI: 10.1038/s42003-022-04263-2
|View full text |Cite
|
Sign up to set email alerts
|

Circ-CREBBP inhibits sperm apoptosis via the PI3K-Akt signaling pathway by sponging miR-10384 and miR-143-3p

Abstract: Male reproductive diseases are becoming increasingly prominent, and sperm quality is an important indicator to reflect these diseases. Seminal plasma extracellular vesicles (SPEVs) are involved in sperm motility. However, their effects on sperm remain unclear. Here, we identified 222 differentially expressed circRNAs in SPEVs between boars with high or low sperm motility. We found that circ-CREBBP promoted sperm motility and inhibited sperm apoptosis by sponging miR-10384 and miR-143-3p. In addition, miR-10384… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…We further predicted the function of the differentially expressed miRNAs in the top 100 and found that these miRNAs (miR-143-3p, miR-152-3p, miR-378a-3p and miR-92a-3p) were related to cell cycle or meiosis. miR-143-3p [68], miR-152-3p [69], miR-378a-3p [70] and miR-92a-3p [71,72] have also been reported to be involved in the regulation of spermatogenesis or semen quality. It is interesting that there is no significant difference in the miRNAs (miR-20, miR-21 and miR-106a) involved in the self-renewal of spermatogonial stem cells [46], indicating that testicular heat stress under the conditions of this study has little effect on spermatogonial stem cells and they have good recovery ability after testicular heat stress injury.…”
Section: Discussionmentioning
confidence: 99%
“…We further predicted the function of the differentially expressed miRNAs in the top 100 and found that these miRNAs (miR-143-3p, miR-152-3p, miR-378a-3p and miR-92a-3p) were related to cell cycle or meiosis. miR-143-3p [68], miR-152-3p [69], miR-378a-3p [70] and miR-92a-3p [71,72] have also been reported to be involved in the regulation of spermatogenesis or semen quality. It is interesting that there is no significant difference in the miRNAs (miR-20, miR-21 and miR-106a) involved in the self-renewal of spermatogonial stem cells [46], indicating that testicular heat stress under the conditions of this study has little effect on spermatogonial stem cells and they have good recovery ability after testicular heat stress injury.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-Akt, MAPK, and Ras signalling pathways are involved in embryonic development. Ding et al [18] discovered that circCREBBP targets miR-143-3p and promotes boar sperm survival and vitality through the PI3K-Akt signalling pathway. Zhao et al [19] revealed that high melatonin levels may induce cell apoptosis, arrest the cell cycle, and inhibit cell growth through the PI3K-AKT signalling pathway, thus interfering with rat embryonic heart development.…”
Section: Discussionmentioning
confidence: 99%
“…These miRNAs exhibited good performance in discriminating patients with PCa from the controls. Moreover, we found that circ-CREBBP in SPEVs can regulate the expression of ssc-miR-143-3p and ssc-miR-10384 in sperm, as well as the expression of MCL1, CREB1, CREBBP, BAX, and CASP3, thereby affecting the apoptosis of sperm . Several studies have used proteomic techniques to detect proteins in SPEVs.…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, we found that circ-CREBBP in SPEVs can regulate the expression of ssc-miR-143-3p and ssc-miR-10384 in sperm, as well as the expression of MCL1, CREB1, CREBBP, BAX, and CASP3, thereby affecting the apoptosis of sperm. 28 Several studies have used proteomic techniques to detect proteins in SPEVs. Yang et al identified 1,474 proteins in human seminal plasma exosomes, which were mainly involved in energy and metabolic pathways.…”
Section: ■ Introductionmentioning
confidence: 99%